Determination of Employee Performance through Emotional and Spiritual Intelligence: A Systematic Literature Review - Andi Nurfiana Haz; Mufidatul Azmi; Nidrah Nidrah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Digital transformation has profoundly altered the landscape of the workplace and triggered high levels of work stress and digital fatigue among employees. This study aims to analyze the influence of emotional intelligence and spiritual intelligence on employee performance through a literature review approach. The research method employed is a literature review by examining scholarly articles retrieved from the Google Scholar database using the keyword “the effect of emotional intelligence on employee performance.” From the initial search, 96 scholarly articles were identified, which were then rigorously screened until 6 articles most relevant to the research objectives were selected. The findings indicate that emotional intelligence has a positive and significant effect on employee performance because it helps individuals manage work stress, build harmonious interpersonal relationships, and improve adaptability in facing modern work dynamics such as hybrid work systems and digital fatigue. In addition, spiritual intelligence has also been proven to positively affect employee performance through the enhancement of integrity, intrinsic motivation, sense of responsibility, and deeper meaning in work. The strong synergy between emotional intelligence and spiritual intelligence has been shown to strengthen employee engagement and create a more humanistic and sustainable work environment. Therefore, organizations need to integrate the development of employees’ emotional and spiritual aspects into formal training programs as a key strategy to improve productivity, mental well-being, and overall work effectiveness in the era of digital transformation.